The Photoshop elements 7 book for digital photographers - Kelby, Scott; Kloskowski, Matt. ([Indianapolis, Ind.] : New Riders, 2009)
"Uncover the inside tips and tricks of the trade for organizing, correcting, editing, sharpening, retouching, and presenting your photos like a pro." -- Cover, p.1.
Includes index.
"User level: Intermediate - Advanced" -- Cover, p.4.
Keywords: Adobe Photoshop elements; Photography -- Digital techniques; Image processing -- Digital techniques -- Handbooks, manuals, etc; Computer graphics